Migrant children unaccompanied - Hosting and Integration Challenges - Belchior-Rocha, H.; Casquilho-Martins, I. (European Association of Schools of Social Work. Conference Madrid 2019, 2019)
This presentation aims to hold a debate on refugee children and adolescents unaccompanied and separated from their families and their process of local integration, based on analysis of secondary data and national and international legislation on child protection. The global number of refugee and migrant children traveling alone has reached a record high, increasing almost five-fold since 2010, the United Nations Children's Fund (UNICEF) points out that at least 300,000 unaccompanied and separated children from their families were registered in about 80 countries in the biennium 2015-2016, the current forecast is 500,000. The cases of unaccompanied and undocumented children reveal one of the most serious hypervulnerability situations. Not only the trauma of forced flight and the separation of relatives, these children still face bureaucratic difficulties of requesting refuge, as well as deprivation of liberty, preventing or delaying access to a range of rights. During the process, the lack of documents makes it difficult to enroll in school, access to health services and benefits of social policies, among other rights.Besides, unaccompanied refugee children and adolescents become an easy target for smugglers and traffickers who aid them in fleeing only to sell them into slavery and forced prostitution with a global percentage of 28%. Consequently, responses are placed on social policies but the challenges to receive and host refugee children separated from the family are also in the need to train professionals involved in the process of requesting refuge and creating a humanized post with a multidisciplinary team to ensure the protection of these children.